Metode Historis: Suatu Kajian Filsafat Materialisme Marx - Fuadi Fuadi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
Abstract: Histories have gone a very long journey throughout the historical journey of mankind and they have been in existence since human beings come to the world. Histories are the human themselves, real human beings who live and fight to do everything possible to own the materials. Histories include the method of thought expressed in the philosophical ideology of Karl Marx to free mankind from dogma and cult. The historical method must start from the basic nature and changes throughout history through human activities and works according to their needs. According to Karl Marx, materials are everything to humans, humans derived from materials, thus they should be in quest for them. Materials are the factor for eternal changes to human beings, and such changes cannot be separated from histories. Therefore, materials cannot be separated from histories themselves as the place for development, formation and perfect human happiness.